Men who have sex with men: a comparison of a probability sample survey and a community based study. Issue 1 (3rd February 2006) - Dodds, J P; Mercer, C H; Mercey, D E; Copas, A J; Johnson, A M
Abstract : We compared characteristics of men who have sex with men (MSM) in a probability sample survey with a community based study in London. The majority of men in both surveys reported male sex partner(s) in the last year but MSM recruited through the population based survey had lower levels of HIV risk behaviour, reported fewer sexually transmitted infections and HIV testing than those recruited from gay venues. Community samples are likely to overestimate levels of risk behaviour among all MSM.